SINTESIS 4–HIDROKSI–5–KLORO–3–METOKSIBENZALDEHID DAN ELUSIDASI STRUKTURNYA - Warsi Warsi; Sardjiman Sardjiman; Sugeng Riyanto (Universitas Ahmad Dahlan, 2012)
The new compound have been synthesis with the chlorination reaction of vanillinwhich aims to produce vanillin chlorinated as raw material in the synthesis ofanalogues of curcumin with Cl substituents on the aromatic ring. The structure of thiscompound have been elucidated. Chlorination of vanillin performed using Cl2 gas,which produced by reaction of kaporit with concentrated hydrochloric acid. Thisreaction takes at temperature 35ºC for 30 minutes, with the AlCl3 as catalyst and THFas solvent. The purity of compound synthesized are determined by melting point andthin layer chromatography. The structure identification of the compound synthesizedconducted using spectrometry techniques, including UV–Vis spectra, infrared spectra(cm-1, KBr) and Nuclear Magnetic resonance proton spectra (, ppm, DMSO-d6,1H–NMR, 500 MHz). Chlorination reaction of vanillin produced yellow crystal of 5chloro–4–hydroxy–3–methoxybenzaldehyde, its melting point is 163.3 to 164.8ºC. Theaverage yield obtained of the this reseach is 40.54%.